2009
DOI: 10.6090/jarq.43.145
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Water Purification Ability of Mangrove (Sonneratia caseolaris) in Mesocosm Tanks

Abstract: Model experiments using mangrove mesocosm tanks were performed two times at the campus of Kasetsart University, Thailand. Replicates of 13 mangrove (Sonneratia caseolaris) saplings were planted in 7 mesocosm tanks and water and soil samples were collected during the 2 experimental periods. The nitrogen removal rate showed 57 and 73 mgN/m 2 /day in the tanks where wastewater from shrimp aquaculture ponds was supplied and exchanged, and 164-425 mgN/m 2 /day in the tanks where the additional nutrients were provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Wong et al (1997) investigated the feasibility of using mangrove wetlands as a sewage treatment facility in the field of 300-hectare natural mangrove intertidal wetlands in Shenzhen, a newly developed city in southern China and the study results showed that those mangrove intertidal wetlands were of great potential for natural wastewater treatment. Shimoda et al (2009) also assessed the water purification ability of Mangrove (Sonneratia caseolaris) in Mesocosm Tanks. Both nitrogen and phosphorus showed high removal rates in the mangrove mesocosm tanks.…”
Section: Valuation Of Water Purification Of Thai Thuy Wetlandmentioning
confidence: 99%
“…Wong et al (1997) investigated the feasibility of using mangrove wetlands as a sewage treatment facility in the field of 300-hectare natural mangrove intertidal wetlands in Shenzhen, a newly developed city in southern China and the study results showed that those mangrove intertidal wetlands were of great potential for natural wastewater treatment. Shimoda et al (2009) also assessed the water purification ability of Mangrove (Sonneratia caseolaris) in Mesocosm Tanks. Both nitrogen and phosphorus showed high removal rates in the mangrove mesocosm tanks.…”
Section: Valuation Of Water Purification Of Thai Thuy Wetlandmentioning
confidence: 99%
“…S. caseolaris has the capacity for municipal wastewater treatment, where COD and BOD5 treatment efficiency is 75%, total phosphorus, total nitrogen and N-NH3 removal efficiency are 60%, 46% and 50% respectively [10]. Besides, S. caseolaris is use for wetland, results showed removed 57 -73 mg/m 2 /day nitrogen and 5.7 -17 mg/m 2 /day phosphorus in tanks using intensive shrimp culture wastewater, with water changes every 3 days [11].…”
Section: Introductionmentioning
confidence: 99%